IMPORTANCE OF MULTIPLE CRITERIA FOR PRIORITY SETTING OF HIV/AIDS INTERVENTIONS. (10th March 2016) - Tromp, Noor; Prawiranegara, Rozar; Siregar, Adiatma; Sunjaya, Deni; Baltussen, Rob
Abstract : Objectives: This study describes the views of various stakeholders on the importance of different criteria for priority setting of HIV/AIDS interventions in Indonesia. Methods: Based on a general list of criteria and a focus group discussion with stakeholders ( n = 6), a list was developed of thirty-two criteria that play a role in priority setting in HIV/AIDS control in West-Java province. Criteria were categorized according to the World Health Organization's health system goals and building block frameworks. People living with HIV/AIDS ( n = 49), healthcare workers (HCW) ( n = 41), the general population ( n = 43), and policy makers ( n = 22) rated the importance of thirty-two criteria on a 5-point Likert-scale. Thereafter, respondents ranked the highest rated criteria to express more detailed preferences. Results: Stakeholders valued the following criteria as most important for the priority setting of HIV/AIDS interventions: an intervention's impact on the HIV/AIDS epidemic, reduction of stigma, quality of care, effectiveness on individual level, and feasibility in terms of current capacity of the health system (i.e., HCW, product, information, and service requirements), financial sustainability, and acceptance by donors. Overall, stakeholders' preferences for the importance of criteria are similar. Conclusions : Our study design outlines an approach for other settings to identify which criteria are important for priority setting of health interventions. For Indonesia, these study results may be used in priority setting processes for HIV/AIDS control and may contribute to more transparent and systematic allocation of resources.